Properties and Roles of γδT Cells in Plasmodium yoelii nigeriensis NSM Infected C57BL/6 Mice - Xie, Hongyan; Xie, Shihao; Wang, Mei; Wei, Haixia; Huang, He; Xie, Anqi; Li, Jiajie; Fang, Chao; Shi, Feihu; Yang, Quan; Qi, Yanwei; Yin, Zhinan; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: Many kinds of immune cells are involved in malaria infection. γδT cells represent a special type of immune cell between natural and adaptive immune cells that play important roles in antiparasite infection. Methods: In this study, malaria infection model was constructed. Distribution of γδT cells in various immune organs and dynamic changes of γδT cells in the spleens of C57BL/6 mice after infection were detected by flow cytometry. And activation of γδT cells were detected by flow cytometry. Then γδT cells in naive and infected mice were sorted and performed single-cell RNA sequencing. Finally, γδT KO mice model was constructed and the effect of γδT cell depletion on mouse T and B cell immunity against Plasmodium infection was explored. Results: Here, splenic γδT cells were found to increase significantly on day 14 after P. yoelii NSM infection in C57BL/6 mice. Higher level of CD69, ICOS and PD-1, lower level of CD62L, and decreased IFN-γ producing after stimulation by PMA and ionomycin were found in γδT cells from infected mice, compared with naive mice. Moreover, 11 clusters were clearly identified in γδT cells by single-cell RNA sequencing (cRNA-seq) based t-SNE analysis. Cluster 4, 5, and 7 in γδT cells from infected mice were found numerous genes involved in immune response. In the same time, the marker genes in each cluster were listed, GO enrichment and KEEG pathway analysis were done. Furthermore, increased parasitaemia, decreased numbers of RBC and PLT, and increased numbers of WBC was found in the peripheral blood from γδT KO mice. Finally, lower IFN-γ and CD69 expressing CD4+ and CD8+ T cells, lower B cell percentage and numbers, and less CD69 expressing B cells were found in the spleen from γδT KO mice, and lower levels of IgG and IgM antibodies in the serum were also observed. Conclusions: Overall, this study demonstrates the diversity of γδT cells in the spleen of Plasmodium yoelii NSM-infected C57BL/6 mice at both the protein and RNA levels, and suggests that γδT cells could help eliminating invasive parasites and promote both cellular and humoral immune responses.